Conversational Implicature in Trevor Noah’s Stand-Up Comedy Show Performance at the 2022 White House Correspondents’ Dinner and Lesson Plan - Nurrohmah, Annisa; Suyatman, Ujang; Listiani, Toneng (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to discuss and describe two aspects: 1) conversational implicature and maxim violations in Trevor Noah's stand-up comedy, and 2) the lesson plan of conversational implicature and maxim violations in Trevor Noah's stand-up comedy using a constructivist approach through Google Forms. A descriptive, qualitative approach based on Grice's implicature theory was employed in this study to analyze 17 of Noah's utterances taken from a YouTube video entitled "Trevor Noah's Complete Remarks at the 2022 White House Correspondents' Dinner" (C-SPAN). The analysis revealed that one utterance can simultaneously violate several maxims. Specifically, 15 general implicatures and two specific implicatures were identified. This study also found that seven utterances violated the maxim of quality, four utterances violated the maxim of quantity, and five utterances violated the maxim of relevance. Six utterances violated the maxim of manner. Noah deliberately used this strategy to make his criticism and satire feel more subtle and less offensive. By breaking the rules, he can funnily convey hidden messages. However, the audience must understand the context of the speech to grasp the implied meaning, as the implied meaning is not always explicitly stated. The lecture plan at a university or college that uses a constructivist approach through Google Form media that involves four initial activities and ten core activity groups.